Anatomiczne i motoryczne podłoże artykulacji - Kabała, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*65.77px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0386);" role="presentation">The author presents the issue of articulation <span dir="ltr" style="left: calc(var(–scale-factor)*250.55px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.06735);" role="presentation">in a <span dir="ltr" style="left: calc(var(–scale-factor)*269.30px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02619);" role="presentation">broad anatomical context. She de<span dir="ltr" style="left: calc(var(–scale-factor)*66.45px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02888);" role="presentation">scribes the most important muscles and structures involved in the process of speak<span dir="ltr" style="left: calc(var(–scale-factor)*66.29px); top: calc(var(–scale-factor)*244.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01715);" role="presentation">ing, and emphasises the importance of a <span dir="ltr" style="left: calc(var(–scale-factor)*231.92px); top: calc(var(–scale-factor)*244.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01228);" role="presentation">holistic approach to <span dir="ltr" style="left: calc(var(–scale-factor)*314.41px); top: calc(var(–scale-factor)*244.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02707);" role="presentation">the human body based <span dir="ltr" style="left: calc(var(–scale-factor)*66.36px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.054);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*78.94px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0069);" role="presentation">the tensegration <span dir="ltr" style="left: calc(var(–scale-factor)*145.02px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990448);" role="presentation">model. She draws attention <span dir="ltr" style="left: calc(var(–scale-factor)*254.90px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02185);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*264.89px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978699);" role="presentation">the role of the fascia and the muscle<span dir="ltr" style="left: calc(var(–scale-factor)*66.33px); top: calc(var(–scale-factor)*272.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.972879);" role="presentation">fascia chains.